2005
DOI: 10.1111/j.1348-0421.2005.tb03708.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Loci to Coronary Arteritis in Animal Model of Kawasaki Disease Induced with Candida albicans‐Derived Substances

Abstract: We have established an animal model of coronary arteritis which is histopathologically similar to that observed in cases of Kawasaki disease (KD), is a well‐known childhood vasculitis syndrome. Coronary arteritis in this mouse model has been induced by intraperitoneal injection of Candida albicans‐derived substances (CADS). Arteritis varied by mouse strain with the highest incidence by 71.1% (27/38) found in C3H/HeN mice, but absent in CBA/JN mice (0%, 0/27), suggesting association of genomic background to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The presence of Candida sequences is intriguing in light of murine models of coronary arteritis based on exposure to Candida glucans comprising mannose, β-1,3-glucan and β-1,6-glucan. Vulnerability to disease varies by mouse strain and is associated with elevated levels of IL-6, TNF-α, and IFN-γ (21,22). Similar to KD, vasculitis can be abrogated by use of i.v.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of Candida sequences is intriguing in light of murine models of coronary arteritis based on exposure to Candida glucans comprising mannose, β-1,3-glucan and β-1,6-glucan. Vulnerability to disease varies by mouse strain and is associated with elevated levels of IL-6, TNF-α, and IFN-γ (21,22). Similar to KD, vasculitis can be abrogated by use of i.v.…”
Section: Resultsmentioning
confidence: 99%
“…We used that model to carry out various studies [6,7,13] and showed that administration of CADS induced systemic vasculitis, including coronary arteritis, in about 70% of mice. This model is considered to be highly useful as an experimental model of KD, especially in view of the fact that it induces granulomatous inflammation of the coronary arteries [7].…”
Section: Discussionmentioning
confidence: 99%
“…In an additional study on Candida -derived agents, C. albicans watersoluble fraction (CAWS) induced severe vasculitis at a higher rate of incidence than CADS in many mouse strains, and there are reports on this valuable animal model system in research on systemic immune responses and inflammatory vascular disease [77][78][79] . The CAWSinduced coronary arteritis is a good model for the histological observation of KD.…”
Section: Animal Models Of Kd Vasculitismentioning
confidence: 99%